Microstructure and Properties of the First-Republic Czechoslovak Circulation Coins - Serak, Jan (Manufacturing Technology Journal, 2018)
In this work, the microstructure and properties of the first-Republic Czechoslovak circulation coins were studied. The variety of the coins at that time was shown. Significant differences in microstructure in the direction of forming and in the normal direction to the surface direction have been confirmed. For some coins, visible features of recrystallization were shown, which suggests the coinage at higher temperatures. The chemical composition of coin alloys was also studied. In most cases, it was consistent with the declared chemical composition by mint. Significant differences in the hardness of the coins were found, which confirmed the different experience of numismatics with the abrasive resistance and the preservation of different coins. The quality of the design and the material composition of the coins confirm the long-standing experience with coinage in the Czech lands, despite the fact that, after the Austro-Hungarian Empire, the mining industry was struggling with big problems (eg stolen raking machines, lack of Czech mining experts). The first-Republic circulation coins represent the best in the history of the Czech and Czechoslovak coinage industry.
Keywords: metallic materials; circulation coins; microstructure; hardness; numismatics